Efficiency of RAFT-synthesized PDMAEMA in gene transfer to the retina - Bitoque, Diogo (2016)
Gene therapy has long been heralded as the new hope to evolve from symptomatic care of genetic pathologies to a full cure. Recent successes in using gene therapy for treating several ocular and haematopoietic pathologies have shown the great potential of this approach that, in the early days, relied on the use of viral vectors, which were considered by many to be undesirable for human treatment. Therefore, there is considerable interest and effort in developing non-viral vectors, with efficiency close to that of viral vectors. The aim of this study was to develop suitable non-viral carriers for gene therapy to treat pathologies affecting the retina. In this study poly(2-(N,N-dimethylamino)ethyl methacrylate), PDMAEMA was synthesized by reversible addition-fragmentation chain transfer (RAFT) and the in vitro cytocompatibility and transfection efficiency of a range of polymer:DNA ratios evaluated using a retinal cell line; in vivo biocompatibility was evaluated by ocular injection in C57BL/6 mice. The results showed that through RAFT, it is possible to produce a defined-size polymer that is compatible with cell viability in vitro and capable of efficiently directing gene expression in a polymer-DNA ratio-dependent manner. When injected into the eyes of mice, these vectors induced a transient, mild inflammation, characteristic of the implantation of medical devices. These results form the basis of future studies where RAFT-synthesized PDMAEMA will be used to deliver gene expression systems to the retina of mouse models of retinal pathologies. Copyright © 2014 John Wiley & Sons, Ltd.